2011
DOI: 10.4103/0970-0218.86518
|View full text |Cite
|
Sign up to set email alerts
|

A study of the swine flu (H1N1) epidemic among health care providers of a medical college hospital of Delhi

Abstract: Background:Influenza viruses cause annual epidemics and occasional pandemics that have claimed the lives of millions. Understanding the role of specific perceptions in motivating people to engage in precautionary behavior may help health communicators to improve their messages about outbreaks of new infectious disease generally and swine flu specifically.Objectives:To study the knowledge and practices of health care providers regarding swine flu and to study the attitudes and practices of health care providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
(10 reference statements)
0
17
2
Order By: Relevance
“…Wearing mask during duty hours was observed in 82.6% of doctors and 85% of nurses. 14 Contrary to our study, Kakade found that 18 (20%) students are had poor knowledge, the majority 31 (62%) had average knowledge and 9 (18%) had good knowledge regarding swine flu and its protective measures. 15…”
Section: Resultscontrasting
confidence: 96%
“…Wearing mask during duty hours was observed in 82.6% of doctors and 85% of nurses. 14 Contrary to our study, Kakade found that 18 (20%) students are had poor knowledge, the majority 31 (62%) had average knowledge and 9 (18%) had good knowledge regarding swine flu and its protective measures. 15…”
Section: Resultscontrasting
confidence: 96%
“…Our findings are almost similar to study among dental practitioners in Nellore of AP conducted by Kappa et al 8 56.7% AYUSH practitioners knew the correct incubation period of H1N1, Our finding was much less than that was observed in 93.2% doctors and 68.8%nurses in a study of swine flu (H1N1) epidemic among health care provider of a medical college of new Delhi. 5 Regarding attitude towards H1N1 in our study, 78.66% practitioners agreed that they are at risk of getting infection by H1N1 virus which is much higher than the perception by dental practitioners at Nellore District. 8 The difference might be probably due to number of cases reported in their community.…”
Section: Discussionmentioning
confidence: 50%
“…This finding is similar to a study conducted by Rajora et al which was conducted in multispecialty teaching hospital in Delhi, India where in all resident doctors knew that influenza was caused by virus and is transmitted by droplets. 5 Our finding on awareness of causative agent of the disease was more than a study done by Datta, et al at Pondicherry which was conducted among paramedical workers in an tertiary care hospital where in 91% workers knew about the agent and mode of transmission of H1N1. 6 A study by Sharma et al showed that symptoms of H1N1 were known to only half of the interns which is very less compared to our general practitioners (75%).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Of these viruses and diseases are EBOLA [4], HIV Aids [5], Swine Influenza H1N1 and H1N2 [6], various strands of flu [7], Severe Acute Respiratory Syndrome (SARS) [8], and Middle Eastern Respiratory Syndrome (MERS) [9]. They have occurred mainly in Africa and the Middle East, but also in some other parts of the world.…”
Section: Introductionmentioning
confidence: 99%